Fuel material in quantification burlap planting of Tectona grandis Linn.F. - Santos, J. C. H.; Sabino, M.; Bortolini, A. T. P.; Silva, A. G. M. F.; Machado Neto, A. P.; Mendes, B. R. S.; Mata, D. P.; Araujo, D. Z.; Pirolla, M. L. (Scientific Electronic Archives, 2017)
This study aimed to evaluate the quantity and fuel moisture content material deposited in planting of Tectona grandis Linn.F with 20 years in the municipality of Sinop - MT. In the study area were installed five plots of 1 m2 within which collected up all the material above ground. The collected material was separated and weighed according to their type (green or dry) and class (leaf, miscellaneous, and branches <0.7 cm, 0.7 cm to 2.5 cm, 2.5 to 7.6 cm and> 7, 6 cm). 100 g were taken. material from each plot to determine the moisture content in the laboratory after drying in an oven at 75 Â° C for 48 hours. The experimental design was completely randomized in a factorial 2x7 (Type X Class) in 5 repetitions, significant means were compared by Tukey at 5% probability. Found 23.2 t ha-1 of dry combustible material in the area. There was no green material because the light conditions caused the tops of planting. There was a significant difference in the amount of combustible material in each class. Classes leaves and miscellany excelled presenting 8.37 Mg ha-1 and 10.29 t ha-1, respectively. Due to the climatic conditions of the season collects a 65.82% moisture content of the material was found.